2005
DOI: 10.2113/53.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Palynostratigraphy, lithostratigraphy and thermal maturity of the Lower Triassic Toad and Grayling, and Montney formations of western Canada, and comparisons with coeval rocks of the Sverdrup Basin, Nunavut

Abstract: In western Canada samples obtained from outcrops of the Lower Triassic Toad and Grayling formations and core samples from coeval subsurface sections of the Montney Formation contain well-preserved palynofloras. These are generally dominated by taeniate bisaccate (e.g. Lunatisporites noviaulensis) and polyplicate gymnosperm pollen (e.g. Ephedripites steevesiae). Acanthomorph acritarchs (e.g. Filisphaeridium sp. cf. F. deunffii, Micrhystridium breve, M. setasessitante, Wilsonastrum colonicum) are often common to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 15 publications
1
23
0
Order By: Relevance
“…Induan (Griesbachian-Dienerian) sedimentary successions range from ~100 m in Alberta to >450 m in the Canadian arctic. Conodonts (see GSA Data Repository Table DR1 1 ) provide biostratigraphic control for the studied stratigraphic sections (Henderson, 1997;Henderson and Baud, 1997;Beatty et al, 2006;Hays et al, 2007) and palynological data supplement these results (Utting et al, 2005).…”
Section: Geologic Settingmentioning
confidence: 87%
“…Induan (Griesbachian-Dienerian) sedimentary successions range from ~100 m in Alberta to >450 m in the Canadian arctic. Conodonts (see GSA Data Repository Table DR1 1 ) provide biostratigraphic control for the studied stratigraphic sections (Henderson, 1997;Henderson and Baud, 1997;Beatty et al, 2006;Hays et al, 2007) and palynological data supplement these results (Utting et al, 2005).…”
Section: Geologic Settingmentioning
confidence: 87%
“…2; L. Lane, personal communication, 2009). Utting et al (2005) concluded Toad Formation strata in an adjacent map area contain Griesbachian (early Induan) palynomorphs. Preliminary palynomorph collections from this section suggest it may be as old as Middle Permian (L. Lane and J. Utting, personal communication, 2009).…”
Section: Locality 5: Toad Formation La Biche River Map Area Southeamentioning
confidence: 97%
“…These mainly consist of source rocks with interbedded thin sandstone or carbonate, and the corresponding shale-formation thickness ratio ranges between 0.6 and 0.9. In the Montney tight oil play in the Alberta Basin, Canada, thick shale formations are dominant, with a small amount of thin sandstone layers and generally low porosity and permeability (Ghanizadeh et al 2015), the average TOC is 2.5 %, and the reservoirs are featured by small monolayer thickness and relatively low gamma in the whole producing section (Utting et al 2005). In the Cretaceous Qingshankou Formation in the Songliao Basin, China, high-quality source rocks with tens of meters thickness are developed and interbedded with a small amount of thin sandstone (Fig.…”
Section: Typical Characteristics Of Tight Oil Playsmentioning
confidence: 99%